Design of solar thermal power plants - Wang, Zhifeng (Academic Press, an imprint of Elsevier, 2019)
Design of Solar Thermal Power Plants introduces the basic design methods of solar thermal power plants for technicians engaged in solar thermal power generation engineering. This book includes the author's theoretical investigation and study findings in solar heat concentrators, a performance evaluation of solar thermal collectors, a numerical simulation of the heat transfer process between complex geometrics, heat transfer through radiation, and more. Containing theoretical descriptions of solar concentrators and receivers, practical engineering examples, and detailed descriptions of site selections for solar thermal power plants, this book has a strong theoretical and practical value for readers.